EFFECTIVENESS OF PRE-HOSPITAL MANAGEMENT TRAINING OF BONE FRACTURE MANAGEMENT ON KNOWLEDGE AND SKILLS OF SOCCER PLAYERS - Nurdiansyah, Ellan Kukuh; Jainurakhma, Janes; Hardianto, Hardianto (Ikatan Lembaga Mahasiswa Ilmu Keperawatan Indonesia, 2020)
This study aims to analyze the effectiveness of training on the knowledge and skills of soccer players about pre-hospital management of fracture management. This study used a pre-experimental approach to the pretest-posttest. The sample in this study was 32 soccer players. The sample collection technique uses purposive sampling. The instrument in this study was a closed-ended questionnaire and observation sheet. The results of statistical tests using the Wilcoxon test with a significance level of 0.05 obtained p-value <0.001. The results of this study indicate that training with simulation methods about pre-hospital management of fracture management is effective in increasing the knowledge and skills of soccer players, and this knowledge is needed to anticipate disability due to injury from a soccer athlete due to fractures with pre-hospital management done in a good and right way.